Geographic information system of station stop points web-based cross-terrain train - Rionald Persada Hidayat (Trigin Publisher, 2023)
North Sumatra is one of the metropolitan cities in Indonesia with a population density in various fields and education and has various kinds of information related to its geographical location, such as information on roads and the location of a train station, school, office, shopping area and so on. Of course, this information is needed by various parties for their respective needs. The absence of media for the community in finding a location makes it difficult for the community to find a place, especially a train station. The public needs information about the geographical location of train station stop points and the mileage of each station digitally so that it is easier for the public to find locations and information about train station stop points. With this problem, then giving the author an idea to raise the title